Lessons from Applying Project Management Techniques in a Ready Made Garments Business - Mahmood Taseen Chowdhury; Saad Hasan; Ashfaque Mohib (International Journal of Technology for Business (IJTB), 2019)
Export oriented clothing sector in Bangladesh, popularly referred to as the Ready-Made Garments (RMG) industry is one of the heavily utilized sourcing hubs for the international clothing retailers and brands. Most of the international retail chains have a local sourcing office tasked with procurement, quality management and logistics issues signifying the importance of Bangladesh as a sourcing hub for the international clothing industry. The nature of the relationship between the international buyers and the local RMG manufacturers is transactional and ad-hoc. The international buyers manage each order with traditional operations processes such as merchandizing, procurement, quality management, shipment and transportation etc. This research using an illustrative case based on a case study argues that performance and overall competitive advantage of all the stakeholders can be improved if individual orders are taken up as project and existing project management knowledge, skills and tools are used. The benefits can be in terms of overall cost minimization, reduction in lead-time, improved efficiency and productivity among others.
Keywords: 650; Project Management; Ready Made Garments; Case Study; Supply Chain Management; International Clothing Industry; Action Research